The good supervisor : supervising postgraduate and undergraduate research for doctoral theses and dissertations - Wisker, Gina, 1951- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
"Provides help for those wanting to develop strategies for effective supervision with a diversity of students on a wide variety of research projects, whether at postgraduate or undergraduate level"--
Machine generated contents note: -- AcknowledgementsIntroductionPART I: FIRST STAGES OF RESEARCH SUPERVISIONThe Role of Supervision and Early Research into the PracticeSupervision DifferencesSupervisors Studying: Development ProgrammesEstablishing and Maintaining Good Supervisory PracticesPART II: ESTABLISHING RESEARCH PROCESSES AND PRACTICESDefining Titles, Research Questions, Conceptual Frameworks and Developing ProposalsEnabling Students to Carry Out a Successful Literature Review and a Theoretical Perspectives ChapterMethodology, Methods and EthicsSupervisory DialoguesEncouraging Good WritingPART III: WORKING WITH STUDENTS - ISSUES FOR SUPERVISORSHelping Students to Help Themselves and Each OtherDealing with Difference: Working with Different Kinds of Learners and Learning StylesSupervising International StudentsStudy and Support at a DistanceGender and Research StudiesA Little too Close to Home: Supervising your Colleagues and/or Other Practice/Professional-based ResearchNew Ways: Supervising Creative Research Work and the PhD by PublicationPART IV:MOMENTUM, COMPLETION AND AFTERWARDS-SUSTAINING RESEARCH COMMUNITIESMaintaining MomentumWriting a Quality Dissertation or ThesisThe Examination Process and ExaminersSupporting Students Towards a Successful PhD VivaSupporting your Student post Viva/ExamLife after ResearchReferencesIndex.
Keywords: Graduate students -- Supervision of; Faculty advisors; Dissertations, Academic; Doctor of philosophy degree; STUDY AIDS / Study Guides; EDUCATION / Higher; EDUCATION / Study Skills